Injuries in women and men handball players, what do coaches need to know? A comprehensive analysis over 3 seasons and 154 games - Andreottola, G.; Ongaro, A.; Ferreira, J.; Crognale, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Handball is a fast-paced Olympic ball game characterized by both defensive and offensive actions aimed at scoring goals. Performance in handball is influenced by a multitude of factors and it involves a range of actions including throws, passes, jumps, hits, blocks and runs. Athletes may experience muscle injuries such as strains and tears due to the rapid movements and accelerations during the game. Furthermore, collisions with opponents and physical contact can lead to traumas such as bruises, contusions and joint sprains. Handball players are also at risk of upper limb injuries, particularly to the hands and wrists, due to the fastball throws and passes. The aim of this study was to monitor number and details of injuries occurring during official Handball matches to enhance current knowledge, awareness and understanding for coaches and practitioners. METHODS: A total of 154 matches of women`s and men`s handball (across 3 seasons - 21/22, 22/23, 23/24) from the national league, national cup and Celtic league of Ireland were analyzed by two independent and experienced sport scientists. A comprehensive report of all injuries, regardless of severity was compiled for the three seasons according to injured body part/region or joint. RESULTS: The data collection resulted in a total of 58 recorded injuries. Despite logistical constraints, key findings reveal a 40% probability of injury during matches, with knee (22.5%), ankle (19%), face (14%), neck (5%), and the face-neck-head complex (20%) injuries being predominant. 60% of injuries occurred in female players (21/22 14W, 8M; 22/23 19W, 10M; 23/24 5W, 2M) CONCLUSION: A gender disparity was evident, indicating a potential need for gender-specific physical preparation and awareness by players, coaches, and practitioners. This analysis also highlighted a need for higher accuracy and consistency when reporting handball injuries and ideally including a comparison with other European leagues and competitions.